CRITICAL REVIEW OF STRATEGIES AND TRENDS IN HEALTH SERVICES AND HOSPITAL MANAGEMENT - 1Mohammed Fares Hadi Alyami, 2Mohammed Yahya Assiri, 3Faris Abdulhmaid Alsulami, 4Saeed Mousa Alghamdi, 5Mohammed Mana Misfer Al Juraib, 6Saleh Hussein Yahya Al Mansour, 7Raddad Wahbi Alnazawi, 8Abdulrahman Marzouq Almutairi, (Chelonian Research Foundation, 2022)
In response to the changing nature of healthcare education, healthcare, and healing center administration are constantly changing. This comprehensive audit assesses various thoughts and improvements in this field. From vital arranging and optimization, the investigation grows to execution change, taking a toll on administration, innovation integration, authority, administration healthcare, and population healthcare. Through a cautious investigation of accessible information, this investigation distinguishes the qualities and shortcomings of the field, giving knowledge to utilization supervisors, healthcare, and approach producers. This audit aims to educate decision-makers by distinguishing regions for improvement and advancing best practices to improve healthcare and healing center management's effectiveness, adequacy, and maintainability. Keywords: Health services, hospital management, strategic planning, quality improvement, cost containment, technology integration, leadership, regulatory compliance, population health management.